FIGURE 6. A, B in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 6. A, B, Dromia erythropus (Edwards in Catesby, 1771), male, cl 21 mm, cw 23.5 mm (MZUSP 33349), habitus dorsal and ventral views, respectively. C, D, Dromia gouveai Melo & Campos Junior, 1999 (junior synonym of D. erythropus), holotype male, cl 90 mm, cw 130 mm (MZUSP 10222), habitus dorsal and ventral views, respectively. Scales: A, B, 10 mm. C, D, 30 mm. Photographs (C, D) by J. Colavite. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 15, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...